Performance of iterative multiuser detection in OWDM-IDMA system - Awatif Rouijel; Benayad Nsiri; Mohammed ET Tolba (2010 5th International Symposium On I/V Communications and Mobile Network, 2010)
Efficiency and adaptivity play a major role in the design of fourth-generation wireless systems (4G). These systems should be efficient in terms of bandwidth and power allocation. Moreover, low complexity transceivers are expected in this type of system. This paper outlines the basic principles of a promising technique for future telecommunications system, called OWDMIDMA (Orthogonal Wavelength-Division Multiplexing-Interleave Division Multiple Access). A comparison with other alternative technologies such OWSS (OWDM spread-spectrum) is provided. Some attractive features of OWMD-IDMA are explained by estimating the BER (bit error rate) of system, including low cost iterative multi-user detection, flexible rate adaptation, spectral and power efficiency.
Keywords: IDMA; iterative detection; CBC; MUD; OWDM; OWSS; DWPT; IDWPT; MAI